Bullyng. Characteristics and forms of reduction in the classroom - Cahuas Orellana, Javier (2014)
This article aims to provide a current topic with increasing importance due to the increased incidence and severity of symptoms, it is the education bullying in Peru. Bullying is a worldwide problem, being found in any school not limited to any institution, primary, secondary, public or private rural or urban. We can also say that there are schools that do not support that bullying occurs between students or ignore the problem or ignore to face. This article aims to explain a set of ideas about what it means or bullying at school, the effects it generates in the school climate, interpersonal relationships of students and some way you can reduce violence in schools.